2013
DOI: 10.1111/jcpe.12114
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions of buccal gingival recessions and requests for treatment

Abstract: This study shows that perception of gingival recessions and the patients' requests for treatment should be evaluated carefully before proceeding with decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
58
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 14 publications
1
58
0
2
Order By: Relevance
“…In a practice‐based evaluation of 500 consecutively treated patients treated with SCTGs (479 involving RC and 21 augmentation procedures), the incidence of infection (0.8%), bleeding (3.0%), swelling (5.4%), and pain (18.6%) was considered very low, and none of the potential predictor factors included in the statistical model (i.e., age, sex, smoking, purpose of the graft, recipient site size, or defect location) were directly associated with such complications 244 …”
Section: Patients’ Preferences (Patient‐centered Outcomes)mentioning
confidence: 99%
“…In a practice‐based evaluation of 500 consecutively treated patients treated with SCTGs (479 involving RC and 21 augmentation procedures), the incidence of infection (0.8%), bleeding (3.0%), swelling (5.4%), and pain (18.6%) was considered very low, and none of the potential predictor factors included in the statistical model (i.e., age, sex, smoking, purpose of the graft, recipient site size, or defect location) were directly associated with such complications 244 …”
Section: Patients’ Preferences (Patient‐centered Outcomes)mentioning
confidence: 99%
“…reported a prevalence of 99.7% of GRs ≥ 1 mm among Brazilian population, and that gender, age, smoking, and high education were risk factors for buccal GR . Nieri and coworkers showed that 80% of patients had one or more buccal GRs and that their perception of GRs was greater on anterior areas, deep GRs, and among young patients . The high prevalence of these mucogingival defects can be attributed to a large variety of predisposing and precipitating factors that include but are not limited to: plaque‐induced inflammation; toothbrush trauma; periodontal disease; malposition; frenum pull; iatrogenic; improper flossing; trauma associated with class II malocclusion; piercing trauma; and orthodontic treatment …”
mentioning
confidence: 99%
“…While dentists view esthetics as the most important reason for root coverage procedures 34 , patients are often not even aware of recessions on their teeth since most of them are asymptomatic 35 . Only 28% of the clinically identified recession sites were perceived by patients as such, with a fraction being associated with dentin hypersensitivity or unaesthetic appearance.…”
Section: Factors To Be Considered For Treating Gingival Recessionmentioning
confidence: 99%